Peranan Komuniti Studi Ilmu Falak (KOSIF) Dalam Menentukan Arah Kiblat Kampus STAIN Sultan Abdurrahman Kepulauan Riau - M. Arbisora Angkat; Rizki Pradana Hidayatulah; Haykal Abdurrahman (Advances in Humanities and Contemporary Studies, 2025)
Astronomy has 170 communities in Indonesia, this is a sign that astronomy has a lot of enthusiasts. The presence of Komunitas Studi Ilmu Falak (KOSIF) in the Riau Islands is considered important because there is no astronomy community in this area, and there are very few astronomers. Komunitas Studi Ilmu Falak (KOSIF) contributes to the community by determining the qibla direction of STAIN Sultan Abdurrahman Kepulauan Riau college. After calculating, it is known that qibla azimuth of STAIN Sultan Abdurrahman Kepulauan Riau college is 293º 03' 35.37" UTSB.